2020
DOI: 10.1039/d0cs00454e
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hosts as in vivo sequestration agents for pharmaceuticals and toxins

Abstract: Supramolecular hosts can act as in vivo sequestration agents for pharmaceuticals and toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 53 publications
0
83
0
Order By: Relevance
“…Cucurbit[n]urils (CB[n]) are macrocycles composed of n glycoluril units, that, owing to their outstanding binding properties, are largely applied for the recognition of several organic molecules and biological analytes ( Figure 6 ) [ 44 , 96 , 97 , 98 , 99 , 100 ]. Thanks to their hydrophobic cavity and highly electronegative carbonyl portals, these macrocyclic containers are particularly suitable to bind positively charged and hydrophobic guests.…”
Section: Receptors For Amino Acidsmentioning
confidence: 99%
“…Cucurbit[n]urils (CB[n]) are macrocycles composed of n glycoluril units, that, owing to their outstanding binding properties, are largely applied for the recognition of several organic molecules and biological analytes ( Figure 6 ) [ 44 , 96 , 97 , 98 , 99 , 100 ]. Thanks to their hydrophobic cavity and highly electronegative carbonyl portals, these macrocyclic containers are particularly suitable to bind positively charged and hydrophobic guests.…”
Section: Receptors For Amino Acidsmentioning
confidence: 99%
“…Supramolecular chemistry, in particular, molecular recognition [1,2] , sensing [3][4][5] and transport [6][7][8][9] have promoted extensive research toward new applications. Out of many synthetic receptors, macrocycles with confined inner spaces distinctly demonstrate the hostguest interaction mechanism: a ring-shaped host possessing a cavity can form an inclusion complex with a suitably sized guest compound.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] Herein, we report that cycHC [8] encapsulates small neutral electron-rich organic molecules, namely, five-and six-membered heterocycles containing sulfur and oxygen atoms. This binding was characterized by 1 H NMR titration and isothermal titration calorimetry (ITC) in solution, and the structure of complexes was investigated by single crystal X-ray diffraction (SC-XRD), solid-state NMR (ssNMR), and thermogravimetric analysis (TGA). We compared the sorption properties of the homologs cycHC [6] and cycHC [8] and found that cycHC [8] is a promising sorbent material that can be applied for selective removal of S-containing hydrophobic neutral guests from water, such as 1,3-dithiolane and α-lipoic acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations